The clinical significance of fibrinogen plasma levels in patients with diffuse large B cell lymphoma. Issue 4 (7th December 2015) - Troppan, Katharina T; Melchardt, Thomas; Wenzl, Kerstin; Schlick, Konstantin; Deutsch, Alexander; Bullock, Marc D; Reitz, Daniel; Beham-Schmid, Christine; Weiss, Lukas; Neureiter, Daniel; Tränkenschuh, Wolfgang; Greil, Richard; et al.
Abstract : Background: Fibrinogen plays a crucial role in the pathophysiology of tumour cell growth, invasion and metastasis. The aim of this study was to evaluate the prognostic significance of pretreatment plasma fibrinogen levels in patients with diffuse large B cell lymphoma (DLBCL) Methods: Data from 372 patients with DLBCL, diagnosed and treated between 2004 and 2013 at two Austrian centres, were evaluated retrospectively. The prognostic influences of plasma fibrinogen levels and other factors, including age, tumour stage and the National Comprehensive Cancer Network-International Prognostic Index, on 5-year overall survival (OS) and 5-year disease-free survival (DFS) were studied using Kaplan–Meier curves as well as univariate and multivariate Cox regression models. Results: Kaplan–Meier analysis revealed that a high fibrinogen plasma level is associated with decreased 5-year OS and 5-year DFS in patients with DLBCL (p<0.001, log-rank test). Furthermore, in multivariate analysis, elevated serum fibrinogen was found to be an independent marker of poor clinical outcome: 5-year OS (HR=1.69, 95% CI 1.06 to 2.72, p=0.029) and 5-year DFS (HR=1.68, 95% CI 1.08 to 2.61, p=0.021). Conclusions: In the current study, we demonstrate that high plasma fibrinogen levels at diagnosis predict poor outcome in patients with DLBCL. Trial registration number: 25-434 ex 12713 and 415-EP/73/127-2012.